Statement of retractions - Գլխ. խմբ.՝ Անրի Ներսեսյան; Պատ. խմբ.՝ Լինդա Խաչատրյան; Խմբ. տեղակալ՝ Ռաֆայել Բարխուդարյան (National Academy of Sciences of Armenia)
This is to notify our respectful reading public that the Editorial Board of the Armenian Journal of Mathematics has retracted two articles from publication.
Keywords: Indexes